Apropriação tecnológica e design centrado no aluno no contexto de ambientes virtuais de aprendizagem - Cardoso, Márcia Coelho (2020)
Due to the constant need for improvement in the quality of education there has been a growing interest in technology tools to support design for teaching and learning in a student-centered way. As a result, the development of tools to support such tasks has in- creased. However, it is not clear what shapes teachers’ design decisions and how tools can best support their design processes. Also, researches on Virtual Learning Environments (VLEs) have shown that teachers usually do not explore VLEs to their full potential and only adopt a limited set of the available tools. The primary goal of the present work is to explore activities and resources available in the VLEs and understand how they can support the technological appropriation and the student centered design. In order to do so, a systematic literature review was executed and an online survey was ran with teachers about this sub- ject. Then, a semiotic inspection was performed on Moodle-PUCRS and GoogleClassroom to analyse the quality of the communication of these VLEs and identify possible improve- ments to this communication. The next step was to execute interviews with teachers that used these VLEs aiming to investigate deeper on technological appropriation and student centered design. The results of these studies showed that the VLEs characteristics pointed by the teaches as relevant to the technological appropriation and student centered design are: simplicity, integration of the VLEs with other techonological tools, content sharing with the students and others teachers, customization possibilities of the VLEs and more ways of interaction with the students.